Description of Chironex indrasaksajiae Sucharitakul sp. nov. (cnidaria, cubozoa, chirodropida): A new species of box jellyfish from the gulf of Thailand - Phuping Sucharitakul (2018)
In this paper a new species of box jellyfish is described. The species, Chironex indrasaksajiae Sucharitakul sp. nov. (Cnidaria: Cubozoa, Chirodropida, Chirodropidae), from the Gulf of Thailand has been identified using morphological structure analysis together with mitochondrial and ribosomal (COI, 16S and 18S) gene data. Results of morphological, molecular and phylogenetic analysis demonstrate that Chironex indrasaksajiae is a species distinct from its congeners. The pedalial canal bend is a character that can be readily used to distinguish this species from its congeners. Clarifying the identity of this box jellyfish is important for understanding box jellyfish biodiversity and has implications for public safety in the Gulf of Thailand.